Construction of a Self-Confidence Scale for Penalty Kick Execution among Youth Football Players (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Self-confidence is one of the most fundamental psychological, decisive factors that dominates the performance of athletes, especially in the tension of competition, such as a penalty kick in football [5]. In spite of the fundamental technical and physical training, a lot of young footballers face performance variations which are traced to psychological factor, especially self-confidence. The objective of the current study was to develop and validate a scientific measure of self-confidence amongst youth football players in relation to penalty-kick scenarios. Methods A descriptive correlational research design was used. Research Population: A representative sample of youth football players in Baghdad Governorate was attained using the stratified cluster sampling. A self-confidence scale was prepared by the researcher based on different psychological studies in the literature, and also was developed in consultation with an expert in the area of research. The original version of the scale contained a number of items across various dimensions such as confidence about sports skills, managing emotions, competition, and outcomes. The validity was determined with expert review and exploratory factor analysis and reliability was verified using Cronbach’s alpha coefficient and the test–retest method. Results showed good levels of construct validity and acceptable internal consistency for the final version of the scale, which may be utilized in both research and applied contexts. The results of a descriptive statistical analysis indicated that the sample's self-confidence level was generally neutral to high. Likewise, there were no statistically significant differences in self-confidence levels between age or years of experience. In summary, the research has resulted in a valid and reliable scale of self-confidence in youth football players that can be confidently used by coaches and researchers to facilitate psychological conditioning to potentially improve performance in critical competitive contexts.